The Role of Waqf in Achieving the Purposes of Islamic Law - Elbachir Askouri (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2024)
Islamic Waqf is an important part of the system of human charity while maintaining the principles and fundamentals aimed at by the Islamic Shari'ah. Waqf has played and still plays an effective role in spreading the syi'ar of Islam, serving the Islamic community in particular and all mankind in general, deepening the bonds of brotherhood among the members of the Islamic state, consolidating the principle of solidarity among them, freeing slaves and abolishing slavery and all forms of servitude. The researcher chose to discuss this topic to identify the reality of the charitable waqf system in Islam. This study seeks to achieve the following objectives:Understanding the concept of waqf in Islamic law, Understanding the concept of the objectives of Islamic law, Shedding light on the relationship of the Islamic endowment with the objectives of Islamic law, Study the importance that Islamic law attaches to charitable endowments and its role in achieving its objectives in the three areas (necessities, needs, and improvements). To achieve the completion of the research, the researcher followed the historical descriptive research method. At the end of the research, the researcher concluded that the endowment plays an important role in achieving its purposes within the scope of necessities, needs, and improvements, and that the purposes of the endowment revolve around creating a permanent and continuous resource to serve humans and preserve their dignity.Wakaf Islam merupakan bagian penting dari sistem kegiatan amal manusia dengan tetap mempertahankan prinsip-prinsip dan dasar-dasar yang dituju oleh Syariat Islam. Wakaf telah dan masih memainkan peran yang efektif dalam menyebarkan syi’ar Islam, melayani masyarakat Islam secara khusus dan seluruh umat manusia secara umum, memperdalam ikatan persaudaraan di antara para anggota negara Islam, mengkonsolidasikan prinsip solidaritas di antara mereka, memerdekakan budak-budak dan menghapuskan perbudakan serta segala bentuk perbudakan. Peneliti memilih untuk membahas topik ini untuk mengidentifikasi realitas sistem wakaf amal dalam Islam. Penelitian ini bertujuan untuk mencapai tujuan-tujuan sebagai berikut: Memahami konsep wakaf dalam hukum Islam, Memahami konsep tujuan-tujuan hukum Islam, Menyoroti hubungan antara wakaf dengan tujuan-tujuan hukum Islam, Mempelajari pentingnya hukum Islam dalam wakaf dan perannya dalam mencapai tujuan-tujuan hukum Islam dalam tiga bidang (kebutuhan, keperluan, dan perbaikan). Untuk mencapai penyelesaian penelitian, peneliti mengikuti metode penelitian deskriptif historis. Pada akhir penelitian, peneliti menyimpulkan bahwa wakaf memainkan peran penting dalam mencapai tujuannya dalam ruang lingkup kebutuhan, kebutuhan, dan peningkatan, dan bahwa tujuan wakaf berkisar pada penciptaan sumber daya yang permanen dan berkelanjutan untuk melayani manusia dan melestarikan martabat mereka. دور الوقف الخيري في تحقيق مقاصد الشريعة الإسلاميةالبشير أسكوريجامعة الأميرة ناراديواس، تايلاندالوقف الإسلامي جزء مهم من منظومة الإحسان الإنساني مع المحافظة على المبادئ والأصول التي تهدف إليها الشريعة الإسلامية. وقد أدى الوقف ولا يزال يؤدي دوراً فعالاً في نشر شريعة الإسلام، وخدمة المجتمع الإسلامي خاصة والجنس البشري كله عامة، وتعميق أواصر الأخوة بين أفراد الدولة الإسلامية، وترسيخ مبدأ التكافل فيما بينهم، وتحرير العبيد وإلغاء الرق وجميع أشكال الاستعباد. وقد اختار الباحث مناقشة هذا الموضوع للتعرف على واقع نظام الوقف الخيري في الإسلام. يؤدي الوقف الخيري دورا بارزا في التنمية بكل أشكالها الاجتماعية والاقتصادية والثقافية داخل المجتمع الإنساني كله، إذ يشكل موردا ماليا أساسيا للعمل الخيري الموجه لخدمة المجتمع، وبناء الحضارة الإنسانية بشكل عام. وللوقف الخيري حضور لافت ومؤثر في كل المجتمعات الإنسانية، مع أن هناك اختلافا في التسمية والأهداف تبعا لخصوصية كل مجتمع. تسعى هذه الدراسة إلى تحقيق الأهداف الآتية: الوقوف على مفهوم الوقف في الشريعة الإسلامية، الوقوف على مفهوم مقاصد الشريعة الإسلامية، بيان علاقة الوقف الإسلامي بمقاصد الشريعة الإسلامية ودراسة الأهمية التي توليها الشريعة الإسلامية للوقف الخيري ودوره في تحقيق مقاصد ها في النطاقات الثلاث( الضروريات والحاجيات والتحسينيات). وللوصول لإنجاز البحث سلك الباحث منهج البحث الوصفي التاريخي. وفي نهاية البحث توصل الباحث إلى أن الوقف يؤدي دورا مهما في تحقيق مقاصد ها في نطاق الضروريات والحاجيات والتحسينيات، وأن مقاصد الوقف تدور حول يجاد مورد دائم ومستمر لخدمة الإنسان، والحفاظ على كرامته.الكلمات المفتاحية: الوقف _ الوقف ومقاصد الشريعة _ دور الوقف في تحقيق الضروريات الخمس